Validitas LKS berbasis problem solving dalam meningkatkan keterampilan 4C pada meteri termodinamika dan gelombang mekanik - Elsa Okta Memori; Yenni Darvina; Syafriani Syafriani; Wahyuni Satria Dewi (Universitas Negeri Padang, 2020)
In the 21st century it is expected to form comparative, innovative, creative, competitive and collaborative people. In the 2013 curriculum which was revised in 2017 contained important points, including the following: 1) strengthening of character education or what we often refer to as PPK. 2) attachment 4C consisting of the ability of creativity (creativity), critical thinking (critical thinking), collaboration (collaboration), and communicating (communication). 3) Literacy. 4) Higher Level Thinking Skills (HOTS). Where I focus more on 4C skills. Reality on the ground does not match the expected conditions. This is obtained from the results of preliminary studies that have been carried out in three high schools in Padang, it appears that in the physics learning process the school has implemented the 2013 curriculum, but according to some teachers the learning process is more comfortable using the friction instruction method. During the learning process the school has used LKS. Use of worksheets will be done if only practicing, while the question is still using worksheets sold by publishers. In the 21st century skills in the application learning process are not maximized nor are worksheets used. Only 21st century skills have been applied to learning, namely collaboration and communication skills. Though critical thinking skills and creativity are quite difficult to apply. This type of research uses Research and Development (R&D) with the Borg and Gall development model. The data source in this study was obtained from the results of validation by 3 validators by giving questionnaire instrumentation which contained six assessment components, namely the feasibility of supporting material content, problem solving models, 4C skills, language feasibility, feasibility of presentation, feasibility of presentation, feasibility of presentation, Graphic LKS. Based on the results of the study, the results of the validation of problem solving-based worksheets in improving 4C skills on thermodynamics and mechanical waves were 83.27%.